STUDY ON THE EFFECT OF STAGE I TEMPERATURE VARIATIONS BETWEEN 660Â°C-700Â°C ON TWO-STEPS HEAT TREATMENT OF MANGANESE STEEL G-X120MN12 - Panji Kresna, Dwiki
The metallic material of manganese steel is generally used for component applications which require a high enough abrasive wear resistance because this type of steel has the ability to undergo a martensitic transformation when its surface is subjected to plastic deformation. In the actual application, the G-X120Mn12 manganese steel must be treated first due to the condition of the as-cast, this material is still hard but brittle. A heat treatment method known as the two-stage heat treatment is usually carried out to handle this problem. To better understand the mechanism of phase transformation and the effect of temperature on the results of the microstructure of this material, in this study, the authors carried out an experiment of this two-stage heat treatment carried out with a variation of stage one temperature of 660°C, 680°C, and 700°C. From the result of this experiment, it can be concluded that the value of the stage one temperature can affect the microstructure related with the value of pearlite phase fraction and the area of fine carbide formed after the two stage heat treatment and it also affects the hardness value of G-X120Mn12 manganese steel.